Landscape Composition Affects Elements of Metacommunity Structure for Culicidae Across South-Eastern Illinois - Trivellone, Valeria; Cao, Yanghui; Blackshear, Millon; Kim, Chang-Hyun; Stone, Christopher (Frontiers in Public Health, 2022)
The interplay among invasive alien vectors and the species assemblage of native potential vectors in areas of range expansion may affect the dynamics of pathogen transmission. In this study we investigate how Aedes albopictus, an invasive mosquito of considerable public health concern fits within mosquito communities at the edge of its range of distribution. This was addressed using a 2-year field survey of mosquitoes in south-eastern Illinois. We found that Ae. albopictus was more broadly distributed in this region than previously realized, with new occurrence records for nine counties. Abundance of this species varied strongly and peaked in locations of low-intermediate overall mosquito species richness. This differed from overall mosquito abundance, as well as abundance of another important vector, Cx. pipiens, for which the abundance-richness relationships were best described with power functions. Metacommunity analyses revealed that mosquito communities showed a non-random distribution with a Clementsian gradient, which suggests a pattern whereby distinct species assemblages are associated with specific habitats or environmental conditions. Land use was a significant underlying factor shaping mosquito community structure and species assemblages. Multivariate analyses showed that while Ae. canadensis and Cx. pipiens complex mosquitoes were associated with high and low proportions of wetlands in the environment, respectively, Ae. albopictus was most strongly associated with urban settlements. This work sheds light on landscape-level processes, such as niche differentiation driven by urban and agricultural development, structuring mosquito communities. We suggest that mosquito community assessments across habitats be incorporated as part of a One Health vector surveillance approach to aid in the goal of prediction and prevention of new and (re-)emerging vector-borne diseases.